Etiology of Acute Undifferentiated Fever in Patients Attending the Emergency Department of a Tertiary Care Hospital - Amjad Hussain, Muhammad Nadeem, Sobia Naeem, Muhammad Khalid, Komal Iqbal, Muhammad Ishfaq, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The presence of a fever is one of the most often reported symptoms to medical professionals working in emergency department. It may be linked to a variety of clinical diseases, ranging from simple viral infections that go away on their own to sepsis. Objective: To assess the etiology of acute undifferentiated fever in patients attending the emergency department Methodology: This retrospective study was carried out at the medicine department, Qazi Hussain Ahmad Medical Complex, Nowshera for duration of one year from 20-July 2020 to 30-July 2021. All the enrolled patients were diagnosed for different diseases like malaria, urinary tract infection, dengue fever, enteric fever and pneumonia. All the data analysis was done by using IBM SPSS version 24. Results: In this study, the male patients were 108 (60%) while female patients were 72 (40%). Out of 108 diagnosed patients, 48 (44.44%) patients were diagnosed with malaria (79.17% P.vivax and 20.87% P.falciparum) followed by dengue fever in 30 (27.78%) patients, enteric fever in 13 (12.04%) patients (92.31% S.typhi, 7.69% S.paratyphi), urinary tract infection in 11 (10.19%) patients and pneumonia was diagnosed in 6 (5.56%) patients. Conclusion: Our study concludes that the predominant etiology of undifferentiated fever was malaria followed by dengue fever. In about 40% of the cases the laboratory tests were inconclusive. Keywords: Acute undifferentiated fever; Etiology; Emergency